1992
DOI: 10.1088/0953-8984/4/50/024
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature metallic conductivity in the semiconductor TlSe having a chain structure

Abstract: The results of experimental investigations of the electrical conductivity, magnetoresistance and Hall effect in the semiconductor TlSe with a chain structure are presented. The measurements of electrical conductivity have been carried out in two directions, i.e. parallel and perpendicular to the crystal c axis (the chain orientation). Galvanomagnetic measurements were made in magnetic fields of up to 60 kOe at different orientations of the magnetic and electric fields. The impurity conductivity is metallic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…It has been shown that TlSe-type crystals are promising materials in device applications as near-and farinfrared sensors, pressure sensitive detectors 8 and as γ-ray detectors. 9 Switching phenomena 10 and lowtemperature metallic conductivity 11 in TlSe have been described successfully.…”
Section: Introductionmentioning
confidence: 94%
“…It has been shown that TlSe-type crystals are promising materials in device applications as near-and farinfrared sensors, pressure sensitive detectors 8 and as γ-ray detectors. 9 Switching phenomena 10 and lowtemperature metallic conductivity 11 in TlSe have been described successfully.…”
Section: Introductionmentioning
confidence: 94%
“…These enhanced properties arise from cooperative interactions being manifested by linear chain (1-D) or layered (2-D) structures, which principally occur in the solids. TlS, TlSe, TlInSe 2 , TlGaS 2 , TlGaSe 2 and TlInS 2 are examples of these anisotropic low-dimensional crystals [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These binary and ternary crystals usually possess chain (TlS, TlSe, TlInSe 2 ) or layered (TlGaS 2 , TlGaSe 2 , TlInS 2 ) structure types.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, reports on: X-ray diffraction, specific heat, dielectric measurements, nuclear magnetic resonance, electron paramagnetic resonance, dielectric sub-millimeter spectroscopy, IR spectroscopy, Raman and Brillouin scattering, inelastic neutron scattering, Mossbauer spectroscopy, etc. have been published [1][2][3][4][5][6][7]. An inclusive review paper on the physical properties of this system may be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The low-dimensionality is also a property of materials that exhibit large anisotropic ratios in some intensive physical properties. For example, pseudo-one-dimensional materials typically have significantly greater optical, magnetic, electrical, and/or mechanical properties in one dimension with respect to the orthogonal directions [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…Most of the physical properties of the TlSe-TlS crystal system have also been investigated. Particularly, diffraction, specific heat and dielectric measurements, nuclear magnetic resonance and electron paramagnetic resonance, dielectric sub-millimeter spectroscopy, IR spectroscopy, Raman and Brillouin scatterings, inelastic neutron scattering, Moessbauer spectroscopy [1][2][3][4][5][6][7] in addition to the metallic conductivity [17] and electronic structure [18] have been reported. An inclusive review paper on the physical properties of this system may be found in Ref.…”
mentioning
confidence: 99%